Advances in production management systems : the path to digital transformation and innovation of production management systems : IFIP WG 5. 7 International Conference, APMS 2020, Novi Sad, Serbia, August 30-September 3, 2020, Proceedings.: the path to digital transformation and innovation of production management systems : IFIP WG 5. 7 International Conference, APMS 2020, Novi Sad, Serbia, August 30-September 3, 2020, Proceedings. Part I ([2020]) - Unknown
No abstract available